Effects of ant predation on the efficacy of biological control agents Hypena Laceratalis Walker (Lepidoptera : noctuirdae) ; Falconia intermedia Distant (Hemiptera : Miridae and Teleonemia scrupulosa Stål (Hemiptera: Tingidae) on Lantana Camara (Verbenaceae) in South Africa - Tourle, Robyn (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2010)
Lantana camara L. (Verbenaceae) remains a highly invasive and ecologically damaging weed in South Africa, despite some 50 years of biological control efforts. Lack of success has been ascribed to varietal differences, climate and predation of agents but these have not been tested. In this study, the effects of ant predation were tested on populations of three biological control agents for L. camara. Colonies of two species, Crematogaster sp. 1 and 2 were investigated. Crematogaster sp. 1 colonies were offered no choice between immature stages of the agents Hypena laceratalis Walker (Lepidoptera: Noctuidae), Falconia intermedia Distant (Hemiptera: Miridae) or Teleonemia scrupulosa Stål (Hemiptera: Tingidae) on lantana shoots. Density-dependent predation on F. intermedia and T. scrupulosa nymphs on lantana shoots was tested using Crematogaster sp. 2 colonies. In choice experiments Crematogaster sp. 2 colonies were offered F. intermedia or T. scrupulosa nymphs on potted lantana plants. Preliminary food trials confirmed that colonies foraged for protein, thereby validating results of no-choice experiments. Crematogaster sp.1 foragers removed 50% of F. intermedia nymphs, followed by 45% of H. laceratalis larvae and only 9% of T. scrupulosa nymphs. Foragers recruited most actively to H. laceratalis larvae and significantly more H. laceratalis biomass was removed than either F. intermedia or T. scrupulosa. A trade-off existed in prey size selection because larger larvae provided considerably more biomass but required forager cooperation and a longer time to subdue than did smaller prey. This increases both forager energy expense and mortality risk by other predators. This study showed that all Crematogaster sp. 1 colonies removed small (≤10mm) H. laceratalis larvae more frequently than larvae larger than 10mm. Thus, of these biological control agents, predators probably prefer small H. laceratalis larvae. Significantly more F. intermedia than T. scrupulosa nymphs were removed by Crematogaster sp. 1, while Crematogaster sp. 2 colonies removed comparable numbers of both agent species. Falconia intermedia nymphs' fast movement triggered a predatory response by these ant species. In contrast, the relatively immobile behaviour of T. scrupulosa nymphs was identified as a highly effective predator avoidance strategy. Since T. scrupulosa nymphs are unable to escape predators by moving, they appear to depend on the presence of alternative prey attracting predator attention. At high agent and/or forager density, T. scrupulosa nymphs attempted escape, but foragers identified them as prey once they moved and caught them. Predation on F. intermedia was also density dependent in that at high nymph and/or forager densities, escape routes were congested and nymphs were more easily caught. Survival of F. intermedia and T. scrupulosa nymphs in particular was low on ant-accessed shrubs in choice experiments and high on ant-excluded shrubs. It is likely that ants significantly depress F. intermedia populations in the field since besides predation, ant foragers probably interrupt F. intermedia feeding and ovipositioning. The combination of parasitism and predation on early instar larvae may explain why H. laceratalis occurs across lantana's range in South Africa but populations remain low. It is unlikely that T. scrupulosa nymphs are habitually preyed on by ant species unless they attract attention by being mobile. Although biological control of L. camara is influenced by climate and physiological defence mechanisms, this study has shown that predation by two ant species severely impacts leaf-feeding agents for L. camara. Thus, it is recommended that future selection of additional agents to control lantana should exclude leaf-feeding .
Keywords: Lantana camara -- Biological control -- South Africa; Weeds -- Biological control -- South Africa; Biological pest control agents -- South Africa; Hemiptera -- South Africa; Miridae -- South Africa; Insect pests -- Biological control -- South Africa; Ants -- Behavior; Lepidoptera; Lace bugs; Noctuidae